2011
DOI: 10.1007/s12530-011-9030-5
|View full text |Cite
|
Sign up to set email alerts
|

Neutrality in evolutionary algorithms… What do we know?

Abstract: Publication informationEvolving Systems, 2 (3): 145-163Publisher Springer Abstract Over the last years, the effects of neutrality have attracted the attention of many researchers in the Evolutionary Algorithms (EAs) community. A mutation from one gene to another is considered as neutral if this modification does not affect the phenotype. This article provides a general overview on the work carried out on neutrality in EAs. Using as a framework the origin of neutrality and its study in different paradigms of EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 84 publications
0
30
0
Order By: Relevance
“…For example, we are considering the use of more devices (agents), we are also planning in using other forms on CI. In particular we are interested in using Evolutionary Algorithms and their novel research on problem hardness (e.g., locality [3], [4], [5], neutrality [2], [6], [11]) to, for example, speed the learning process up.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we are considering the use of more devices (agents), we are also planning in using other forms on CI. In particular we are interested in using Evolutionary Algorithms and their novel research on problem hardness (e.g., locality [3], [4], [5], neutrality [2], [6], [11]) to, for example, speed the learning process up.…”
Section: Discussionmentioning
confidence: 99%
“…As argued in [16], much of this contention stems from the overly complex problems, representations, and search algorithms used in these investigations, which make it difficult to tease apart the effects of neutrality from other confounding factors. In addition, neutrality is often artificially added to the problem representation and little attention is paid to how this alters the fitness landscape.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of neutrality in GP is a contentious topic [16]. While some studies have found no benefit [7,44,45], others have claimed that neutrality buffers against deleterious genetic perturbation [20,46,57] and reduces the risk of premature convergence through an expansion of the search space [12,18].…”
Section: Introductionmentioning
confidence: 99%
“…In other words synonymous redundancy (redundancy of genotypic neighbours) has the same effect as a small divergence of genotypic neighbours. Whether neutrality is beneficial in general is a complex question considered in detail in some previous work [11,12,16,19,37,44,45,61]; this issue deserves consideration as we will see. The situation is summarised (for discrete-valued phenotypic distances) in Table 1.…”
Section: Extending the Definition Of Locality To The Genotype-fitnessmentioning
confidence: 92%